Successful Confirmation of Dual Genital Herpes Co-Infection with Herpes Simplex Virus 1 and Herpes Simplex Virus 2 Using Unbiased Metagenomic Next-Generation Sequencing - Chun Kiat Lee; Sau Yoke Ng; Chean Nee Chai; Yu Feng Lim; Tiffany Jingyan Hu; Ogestelli Fabia Lee; Gabriel Yan (Viruses, 2023)
Dual co-infection with both HSV-1 and HSV-2 is rare, with few cases reported in the literature. In this case report, we describe the successful use of unbiased metagenomic next-generation sequencing (mNGS) as a rapid and alternative method for confirming dual genital herpes co-infection. Our case involves a 74-year-old woman who presented with genital lesions and initially tested positive for both HSV-1 and HSV-2 via the Luminex ARIES HSV 1&2 assay. The entire mNGS process, from nucleic acid extraction to result analysis, was completed in less than 48 h. Using mNGS, we identified mapped reads specific to either HSV-1 or HSV-2 and screened the sequences to rule out mis-genotyping by the Luminex ARIES assay. Notably, the generated sequences can reveal sequence variations within multiple gene regions, demonstrating the potential of mNGS for identifying novel HSV-1 and HSV-2 variants. Our findings suggest that mNGS can serve as a rapid and reliable alternative confirmatory method for dual genital herpes infections, providing valuable information to guide appropriate treatment options for patients. By eliminating the need for prior knowledge of causative agents, mNGS offers an unbiased approach for detecting and characterizing viral co-infections.